The Influence Of Training Methods Single Leg Hop And Double Leg Hop Against The Explosive Power Of The Leg Muscles Of PJKR Stkip Yapis Dompu Students - Munandar, Rizky Aris; Hidayat, Taufiq; Pratama, Sandi Achmad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study uses a